VIDEOTAPE INSTRUCTIONAL PACKAGE AND ITS EFFECT ON STUDENTS’ ACHIEVEMENT AND RETENTION OF CONCEPTS IN CHEMISTRY AT SECONDARY SCHOOLS - Nwobasi Chukwudi Samuel & Nwani Pius Okorie (International Journal of Research Science and Management, 2020)
This study examined videotape instructional package and its effect on students’ achievement and retention of concepts in chemistry. One hundred (100) SSII chemistry students in Abakaliki Local Government Area of Ebonyi state southeast Nigeria made up the sample for this study. The sample was divided into two groups; one formed the experimental group taught with videotape instructional package while the other formed the control group taught with traditional method. The instrument for data collection was 60 items multiple choice questions in chemistry. Analysis of data was done using mean, standard deviation, and t-test statistics. The results revealed that videotape instructional package for teaching chemistry significantly improved achievement and retention of concepts capability of students than the traditional method. It was then recommended that videotape instructional package be used for instruction among students in Ebonyi state southeast Nigeria.